The Glycemic Index and Organoleptic Test of Pekawai (Durio kutejensis) Chips - O. A. Lestari; S. Purwayantie (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2017)
Pekawai fruit (Durio kutejensis) is one of the durian species that grows wild in the forests of West Kalimantan. It is known by its yellow-golden orange flesh color. It does not have an unpleasant smell and has non sticky flesh, which makes it attractive and has potential to be healthy snacks such as fruit chips. This research was conducted to find out consumer preference by doing organoleptic and glicemic index test. The glycemic index test has been done by 10 volunteers and organoleptic test conducted using scoring and hedonic methods with 35 panelists. Data analyzed with descriptive method. The results showed that pekawai chips has low glycemic index (12) and were liked by the panelists. The results showed that pekawai fruit, the exotic local fruit from West Kalimantan has big potential to be developed as a snack, which has high economic value and safe to be consumed by diabetics. Keywords: glycemic index, pekawai, fruit, chips